DEVELOPMENT AND ASSESSING THE EFFECTIVENESS OF CROSS-BORDER COOPERATION BETWEEN UKRAINE AND POLAND IN THE FIELD OF TOURISM - Атаманчук, Зарина; Макогин, Зоряна (SWorldJournal, 2021)
Poland is one of our closest neighbors and our strategical partner. Given the fact that Poland is a member of the EU, Ukraine is extremely interested in developing strategic relations with it. Today, cooperation between two countries takes place in almost